Approach to Victoria Álvarez Ruiz’s Life and Work - Arias Chachero, Patricia (Madrygal. Revista de Estudios Gallegos, 2018)
Last September 23th, a main specialist on Rosalía de Castro’s biography died in Vigo: the secondary school teacher Victoria Álvarez Ruiz de Ojeda. Only 57 years old, she was a rigorous researcher who valued objective documentation and contrasted information. Discreet, away from Galician cultural circles, many people knew her work but few ones knew the person. For thirty years she made important contributions about Rosalía’s family, about her correspondance and literary friendships. In addition to this, she released other relevant documents and a book that contains a collection of comedies represented at the Liceo de la Juventud in Compostela, by this key figure of the Galician Rexurdimento. As a researcher, she carried out studies on Eduardo Blanco Amor, Manuel Curros Enríquez, Valentín Lamas Carvajal, Manuel Murguía and different figures of Galician literature. The scholar born in Vigo leaves a lot of unpublished works behind. Before dying, she expressed the wish that her valuable library about Rosalía de Castro library is kept in the University of Santiago de Compostela.